Carbohydrate Partitioning, Growth and Ionic Compartmentalisation of Wheat Grown under Boron Toxic and Salt Degraded Land - Tayyaba Naz; Muhammad Mazhar Iqbal; Javaid Akhtar; Muhammad Saqib; Muqarrab Ali; Mazhar Iqbal Zafar; Bernard Dell; Rahul Datta; Mohammad Javed Ansari; Subhan Danish; Shah Fahad (Agronomy, 2022)
Cultivation of crops in salt-affected soils is a major challenge for growers. Despite the use of multiple amendments, salinity stresses adversely affect the crops to some extent. On the other hand, imbalance in the use of boron (B) as a nutrient also creates toxicity. Mismanagement of B fertilizer application decreases the growth and yield of crops. It is necessary to study in depth the adverse effects of salinity and B toxicity. This is why the current research work was conducted in a glass house at Murdoch University, Perth, Australia. The aim of study was to investigate the influence of salinity and B toxicity on carbohydrate partitioning, growth, and ionic composition of two Australian wheat varieties. There were four treatments, i.e., control, high B (15 kg ha−1), salinity (15 dS m−1), and B + salinity. The results showed that the salt-tolerant Halberd (HB) variety accumulated more Na+, B, and Cl− in their leaf sheath and kept the leaf blades free of these toxic ions as compared to the sensitive variety Westonia (WS). Water-soluble carbohydrate (WSC; i.e., glucose, sucrose, fructose, and fructans) concentration increased in response to individual as well as combined constrains of soil salinity and toxic B in the leaf blade of both tolerant and sensitive wheat varieties, but the increase was higher in the tolerant variety as compared to the sensitive one. The concentration of WSCs in leaf sheath of the salt-tolerant wheat variety was increased in response to stress conditions, but those remained low in salt-sensitive ones. Therefore, the salt-tolerant HB genotype was found to be a good source for future wheat breeding programs or to be grown by farmers in B toxic, saline, and B toxic–saline conditions.